Kualiti kehidupan pesakit yang menjalani pembedahan pintasan graf arteri koronari (CABG) - Mohd Khairul Zul Hasymi, Firdaus (PPSP, Universiti Sains Malaysia, 2007)
Heart disease is known to be one of the contributions to mortality rate in the world. Fitzegerald, Tennen, Affleck & Pransky, 1993, stating that coronary artery disease is one of the contributors to the mortality rate in the Western population. Meanwhile, in Malaysia, heart disease is the second caused of mortality with the 14.52% mortality rate in Malaysian population. There are two way in giving treatment to the heart patient via medication or surgery. Besides, in certain cases surgery is the best way as a treatment to the heart problem. CABG is one the numbers of surgery perform to treat the heart problem. This surgery is to rebuild blood vessels as to ensure that heart can be function well. Furthermore, this surgery is performed as to increase the quality of life of heart patient as quality of life is influenced by the disease itself. OBJECTIVE. This research is done to see the influence of heart disease to the patient himself. Moreover, the changing of quality of life also assessed to see how good after CABG is performed. Besides, the inter relationship factor between socio demographic and quality of life is try to recognized. This research also tries to recognize the limitation facing by the heart disease patient. METHODOLOGY. This is descriptive comparison study which had done in Ward 2 Krista! and 2 Fairuz . Sample was selected by convieniece sampling and included 30 respondent. The respondent is fulfill the inclusion criteria. The criterias are male or female patient and undergoing the CABG surgery in HUSM. The data collected since December 2006 till mid of Mac 2007 and using Short Form 36 (SF36) questionnaires. This questionnaire is evaluating the aspect quality of life. Patient was approached twice by researcher. First meeting done before patient undergoing to CABG procedure and last approach is after 4 weeks of surgery. The same questionnaire is used. The data analyzed by using 'Statistical Package Social Science' (SPSS) version 13.0 software by descriptive. Paired t test also done which the p value is less than 0.05, giving significant value and null hypothesis rejected. RESULTS. The quality of life patient post surgery is better than before. By the respondents total score the quality of life still in moderate. The highest total score before surgery is performed is 86.00 the lowest score is 73.00. However, after surgery is performed, even the quality of life still in moderate, but the score is increase, the highest 124.00 and the lowest 86.00. After paired t-test done, the p value is 0.000 which lower than 0.05. Null hypothesis is rejected. Besides, smoker is in high risk to get heart disease, meanwhile male are prominent to get heart disease compared to the female. Limitation in the heart patient also identified. CONCLUSION. Quality of life is one of the indicator in our life as us concern about our health. The higher value of quality of life, the healthier life we get. The quality of life among heart patient usually in moderate however it can be upgrade. It is proven by this research, that quality of life among patient undergoing CABG surgery got a better quality of life after performing CABG. In conclusion, for the heart patient, surgery is one of the treatments to get a better life and improve for a healthier heart and life.